Analyzing the potency of Viscosity Modifying Agents on the Characteristics and Static Segregation of Fresh and Hardened Fluid Concrete - Faiza M’hamdi; Othmane Boukendakdji; Karim Ezziane; Taha-Hocine Douara (The Journal of Engineering and Exact Sciences)
Self-compacting concrete (SCC) represents a recent advancement in the field of concrete technology due to its ease of handling and placement. In order to regulate the internal integrity of the concrete, a supplementary mixture component is employed. The term used to refer to this particular component is a viscosity-modifying agent (VMA). Different quantities of VMA were incorporated into the concrete mixture in order to evaluate its performance in both the fresh and hardened states. This study focused on the impact of VMA (Viscosity Modifying Agent) on various characteristics of concrete mixes. Specifically, the features under examination included flowing time, slump flow, flow time into a 500-mm diameter, and resistance to vertical segregation. In contrast, a measurement was conducted on the compressive strength of the cured concrete. The utilization of the column of segregation test allows for the identification and assessment of static segregation in SCC mixtures. This test offers a direct quantitative determination of the stability of segregation in fresh concrete. The purpose of this experiment is to determine the precise quantity of coarse aggregate with a diameter above 8 mm present within a specimen of 300 mm in height. This can be achieved by conducting sedimentation tests at a specific time interval of 30 minutes after the pouring of concrete. The research results indicate that the addition of VMA had a substantial impact on the rheological characteristics of the concrete mixture. It effectively stabilized the mixture, minimized static segregation, and improved the compressive strength when compared to the reference mixture without VMA. Furthermore, a comprehensive illustration of the segregation phenomenon is provided by the column of static segregation tests.